Klasifikasi Pertumbuhan Sektor Pada Produk Domestik Regional Bruto (PDRB) dan Pertumbuhan Ekonomi di Kabupaten Manokwari Tahun 2013 – 2017 - Tika Adolfina Urbinas; Danny Erlis Waimbo; Rumas Alma Yap (Lensa Ekonomi, 2020)
The purpose of this study is to determine the basic and non-basic sectors, the growth rate of each sector towards economic growth, the contribution of each sector to economic growth, to classify sector growth in the Gross Regional Domestic Product (GRDP) based on the Typology Klassen matrix of Manokwari Regency. and West Papua Province. The data used in this study is in the form of time series data from Gross Regional Domestic Product (GRDP) in the period 2013-2017. By using the Location Quotient (LQ) analysis method and Klassen Typology analysis, 10 basic sectors are obtained, namely: Mining and Excavation, Electricity and Gas Procurement Sector, Water Supply Sector, Waste Management and Recycling, Transportation and Warehousing Sector, Food Accommodation Supply Sector and Drinking, Information and Communication Sector, Financial Services and Insurance Sector, Real Estate Sector, Corporate Service Sector, and Health Services Sector and Social Activities. Whereas the Klassen Typology Matrix shows that the sectors that are developed and growing rapidly in Manokwari Regency and West Papua Province include the Mining and Excavation Sector, Water Supply Sector, Waste Management, Waste and Recycling Sector, Information and Communication Sector, Real Estate Sector, Government Administration, Defense and Compulsory Social Security. Tujuan dari penelitian ini ialah untuk mengetahui sektor basis dan sektor non basis, laju pertumbuhan masing-masing sektor terhadap pertumbuhan ekonomi, kontribusi masing-masing sektor terhadap pertumbuhan ekonomi, mengklasifikasi pertumbuhan sektor pada Produk Domestik Regional Bruto (PDRB) berdasarkan matriks Tipologi Klassen Kabupaten Manokwari dan Provinsi Papua Barat. Data yang digunakan dalam penelitian ini adalah berupa data time series dari Produk Domestik Regional Bruto (PDRB) dalam periode tahun 2013-2017. Dengan menggunakan metode analisis Location Quotient (LQ) dan Analisis Tipologi Klassen diperoleh 10 sektor basis yaitu: Pertambangan dan Penggalian, Sektor Pengadaan Listrik dan Gas, Sektor Pengadaan Air, Pengolahan Sampah Limbah dan Daur Ulang, Sektor Transportasi dan Pergudangan, Sektor Penyediaan Akomodasi Makan dan Minum, Sektor Informasi dan Komunikasi, Sektor Jasa Keuangan dan Asuransi, Sektor Real Estate, Sektor Jasa Perusahaan, dan Sektor Jasa Kesehatan dan Kegiatan Sosial. Sedangka Matriks Tipologi Klassen menunjukkan bahwa sektor yang maju dan tumbuh dengan pesat di Kabupaten Manokwari dan Provinsi Papua Barat antara lain Sektor Sektor Pertambangan dan Penggalian, Sektor Pengadaan Air, Pengolahan Sampah, Sektor Limbah dan Daur Ulang, Sektor Informasi dan Komunikasi, Sektor Real Estate, Administrasi Pemerintah,Pertahanan dan Jaminan Sosial Wajib.